Strategic Financial Management in Islamic Early Childhood Education: Facility Development and Student Enrollment Growth - Haikal; Adiyono; Jumadi Ramadani (Chalim Journal of Teaching and Learning, 2026)
This study aims to examine how strategic financial management is implemented in Islamic early childhood education and how it contributes to facility development and student enrollment growth. Grounded in a qualitative descriptive case study approach, this research has been performed at an Islamic Integrated Early Childhood Education institution (PAUD Islam Terpadu Cendekia) in Indonesia. Data for this study were derived from in-depth interviews of key institutional actors (the principal or head teacher, treasurer, representatives from the foundation, and teachers), direct observations, and analysis of financial documents of the institution. The study found the following: Financial management allows for coordinated annual planning, with project priorities on facilities determined by functions rather than aesthetics, followed by adaptive strategies to external funding uncertainties, such as delays in government assistance. When the budget is allocated, first comes teacher welfare, followed by learning-sustaining facilities and child safety, while aesthetics come last. The improvements of these facilities do not directly increase enrollment but rather work on parental trust and word-of-mouth recommendations about the institution from their previous experiences and those of others, bypassing marketing activities. This raises further challenges to the traditional assumptions in education finance which have explicitly theorized a direct link from funding to enrollment. Instead, this research shows that funding works through the intervening variable of parental trust on enrollment. In conclusion, strategic and relational financial management is extremely important in sustaining institutional quality and credibility among Islamic early childhood education providers. From here, the research contributes to the educational management science by proposing a refined conceptual model associating strategic planning, facility development, parental trust, and enrollment growth toward faith-based early childhood contexts.